Early Gains in Renal Function Following Implantation of HeartMate II Left Ventricular Assist Devices May Not Persist to One Year. Issue 4 (July 2017) - Hasin, Tal; Grupper, Avishay; Dillon, John J.; Maleszewski, Joseph J.; Li, Zhuo; Topilsky, Yan; Frantz, Robert P.; Edwards, Brooks S.; Pereira, Naveen L.; Maltais, Simon; Stulak, John M.; Joyce, Lyle; et al.
Abstract : Renal function improves early after left ventricular assist device (LVAD) implantation but later decline has been observed. We sought to determine the occurrence and evaluate possible causes for this decline. In 62 consecutive patients with HeartMateII LVAD with available calculated glomerular filtration rate (GFR, ml/min/1.73 m 2 ) 1 year after implant, GFR was assessed repeatedly and possible predictors for decline from 3 to 12 months were investigated. Post-mortem renal specimens for patients supported with an LVAD were evaluated. GFR 54.5 ± 19.5 at admission increased to 66.4 ± 22.3 preoperatively and to 79.2 ± 30.1 1 month after implantation. Subsequently at 3 months GFR declined to 74.7 ± 25.4, at 6 months to 68.8 ± 23.1, and 1 year after implant to 63.9 ± 17.7. Glomerular filtration rate at 1 year was significantly lower ( p < 0.0001, p < 0.0001, p = 0.005) than GFR 1, 3, and 6 months after implant. Early rise in GFR after surgery was not associated with late decline. Shorter bypass time ( β = −0.09, p = 0.048) and higher albumin 3 months after LVAD ( β = 14.4, p = 0.025) were significantly associated with less later decline in GFR. Arteriosclerosis was identified in autopsy renal specimens. In conclusion, early gains in renal function after LVAD implant are not sustained in many patients. Patient, device, and operative factors may influence long-term renal function in these patients.